Higher expression of Th1/Th2-related cytokines in the intestine of Wistar rats with ligature-induced periodontitis - de Mello-Neto, João Martins; Elangovan, Gayathiri; Ervolino, Edilson [UNESP]; Johnson, Newell Walter; Gustafsson, Anders; da Silva Figueredo, Carlos Marcelo (Wiley, 2023)
Objective: This study aimed to investigate the impact of ligature-induced periodontitis (LIP) on histopathological and immunological outcomes in the colon of Wistar rats. Background: It has been repeatedly shown that inflammatory bowel disease (IBD) patients are at higher risk of developing periodontitis and presenting worse oral health than non-IBD patients. However, whether the chronic inflammatory process around teeth contributes to the pathophysiology of IBD needs to be further explored. Materials and Methods: Thirteen Wistar rats were allocated into LIP (n = 7) and controls (n = 6). Half of the colon was processed for histopathological analyses and immunohistochemical (CD45); the other half was homogenized for immunological analyses. Periodontal destruction was confirmed by measuring the distance from the cementum-enamel junction to the mandible's apical position of the mesial interproximal bone. The immunological analyses were performed with the Bio-Plex Th1/Th2 assay. Results: There was a significantly higher interproximal bone loss in LIP compared to controls. The LIP group showed a moderate infiltrate of inflammatory cells, predominantly mononucleated cells in the intestinal tissues. There was significantly higher expression of GM-CSF, IFN-γ, IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-10, IL-12 (p70), IL-13, and TNF-α in the intestinal tissues of LIP group compared to controls. Conclusion: Ligature-induced periodontitis was associated with an overexpression of Th1/Th2-related cytokines in the colon of Wistar rats.
Keywords: cytokines; inflammatory bowel diseases; intestine; periodontitis; rats